AKAD MURABAHAH AND IJARAH AND THEIR APPLICATION IN ISLAMIC FINANCIAL INSTITUTIONS - A.Habibi A; Syufa’at (JOURNAL EQUITABLE, 2024)
The increase in people's needs is hampered by busyness and inability to meet their needs so that people need alternatives to help them fulfill their needs. Sharia Financial Institutions (LKS) have emerged as an alternative for people to meet their needs. The main product that LKS offers to the public is murabahah because there is little risk in its application. However, the murabahah application has caused a lot of criticism among the public. Islamic banks are often referred to as "murabahah banks" because murabahah and ijarah dominate and modifications to the murabahah and ijarah applications are considered the same as transactions at conventional banks. This study is a literature review with deductive analysis, namely the author analyzes from general to specific so that conclusions can be drawn. The results of this research conclude that the murabahah application in sharia banking makes sharia banks as fund providers, not sellers. The murabahah and ijarah contracts in classical jurisprudence have also undergone many modifications. These modifications to the murabahah and ijarah contracts have given rise to criticism among the public. Modifications to the murabahah contract include the murabahah contract which binds the customer before the bank has the goods the customer wants, giving rise to bai' ma'dum, murabahah lil amri bi al-syira' which is considered haram by some scholars because it is a loophole for usury, and murabahah bil wakalah which is legally permissible.